Accessing structurally diverse near-infrared cyanine dyes for folate receptor-targeted cancer cell staining - König, Sandra G.; Krämer, Roland (Chemistry - a European journal, 2017)
Folate receptor (FR) targeting is one of the most promising strategies for the development of small-molecule-based cancer imaging agents considering that the FR is highly overexpressed on the surface of many cancer cell types. FR-targeted conjugates of near-infrared (NIR) emissive cyanine dyes are in advanced clinical trials for fluorescence-guided surgery and are valuable research tools for optical molecular imaging in animal models. Only a small number of promising conjugates has been evaluated so far. Analysis of structure-performance relations to identify critical factors modulating the performance of targeted conjugates is essential for successful further optimization. This contribution addresses the need for convenient synthetic access to structurally diverse NIR-emissive cyanine dyes for conjugation with folic acid. Structural variations were introduced to readily available cyanine precursors in particular via C−C-coupling reactions including Suzuki and (for the first time with these types of dyes) Sonogashira cross-couplings. Photophysical properties such as absorbance maxima, brightness, and photostability are highly dependent on the molecular structure. Selected modified cyanines were conjugated to folic acid for cancer cell targeting. Several conjugates display a favorable combination of high fluorescence brightness and photostability with high affinity to FR-positive cancer cells, and enable the selective imaging of these cells with low background.